Management Science in the World of Today and Tomorrow - Dantzig, George B. (Management Science, 1967)
Operations Research or Management Science, two names for the same thing, refers to the science of decision and its application. In its broad sense, the word “cybernetics,” the science of control, may be used in its place. This science is directed towards those tasks that humans have not yet delegated to machines. Tasks involving human energy and (as we have seen) those involving simple human control have already been conceded to machines even though they have not been fully taken over by them. It is the automation of higher order human decision processes that is the last citadel.